ON THE DICTIONARIES OF THE INSTITUTE FOR MACEDONIAN LANGUAGE (Philological Studies, 2023)
The purpose of this paper is to present part of the lexicographical work of the Institute for the Macedonian Language "Krste Misirkov" – Skopje, on the occasion of its jubilee – 70 years since its foundation. The starting point is the Dictionary of the Macedonian language with Serbocroatian[1] interpretations, which was and remains more than a dictionary. [1] During the period of the SFRY's existence, the official language was Serbocroatian.